Strengthening of the annual temperature cycle in the mid-latitudes of Northern Hemisphere - Tao Tang; Xuhui Lee; Junji Cao (Discover Geoscience)
Abstract The annual temperature cycle (ATC), defined as the surface temperature difference between summer and winter, plays a crucial role in controlling the phenology of biological systems (Sparks and Menzel in Int J Climatol 22(14):1715–25, 2002) and in global and regional circulation patterns (Schott and McCreary in Prog Oceanogr 51(1):1–123, 2001), (Adam et al. in J Clim 29(9): 3219–3230, 2016). Contrary to previous studies which report a decreasing trend in the ATC worldwide (Mann and Park in Geophys Res Lett 23(10):1111–4, 1996), (Wallace and Osborn in Climate Res 22(1):1–11, 2002), recent studies suggest an increasing ATC trend in the mid-latitude regions (Wang and Dillon in Nat Clim Chang 4(11):988–92, 2014). Although the trend may bear anthropogenic fingerprints, the underlying mechanism remains elusive. Using atmospheric reanalysis data and observational records, we confirm that the increasing trend in the ATC occurred during 1980–2020, mainly in the West North America, Mediterranean region and part of North Asia. The main driver of this ATC change is the faster increase in the incoming radiation on the land surface in the summer as a result of the buildup of water vapor and reduction in cloudiness. This increase was further amplified by continental dryness in the summer.